Early Intravenous Delivery of Human Brain Stromal Cells Modulates Systemic Inflammation and Leads to Vasoprotection in Traumatic Spinal Cord Injury. (31st May 2016) - Badner, Anna; Vawda, Reaz; Laliberte, Alex; Hong, James; Mikhail, Mirriam; Jose, Alejandro; Dragas, Rachel; Fehlings, Michael
Abstract : This work demonstrates a therapeutic approach whereby a minimally invasive cell-transplantation procedure can effectively reduce secondary damage after spinal cord injury through systemic immunomodulation. Abstract: : Spinal cord injury (SCI) is a life-threatening condition with multifaceted complications and limited treatment options. In SCI, the initial physical trauma is closely followed by a series of secondary events, including inflammation and blood spinal cord barrier (BSCB) disruption, which further exacerbate injury. This secondary pathology is partially mediated by the systemic immune response to trauma, in which cytokine production leads to the recruitment/activation of inflammatory cells. Because early intravenous delivery of mesenchymal stromal cells (MSCs) has been shown to mitigate inflammation in various models of neurologic disease, this study aimed to assess these effects in a rat model of SCI (C7-T1, 35-gram clip compression) using human brain-derived stromal cells. Quantitative polymerase chain reaction for a human-specific DNA sequence was used to assess cell biodistribution/clearance and confirmed that only a small proportion (approximately 0.001%–0.002%) of cells are delivered to the spinal cord, with the majority residing in the lung, liver, and spleen. Intriguingly, although cell populations drastically declined in all aforementioned organs, there remained a persistent population in the spleen at 7 days. Furthermore, the cell infusion significantly increased splenic and circulating levels of interleukin-10—a potent anti-inflammatory cytokine. Through this suppression of the systemic inflammatory response, the cells also reduced acute spinal cord BSCB permeability, hemorrhage, and lesion volume. These early effects further translated into enhanced functional recovery and tissue sparing 10 weeks after SCI. This work demonstrates an exciting therapeutic approach whereby a minimally invasive cell-transplantation procedure can effectively reduce secondary damage after SCI through systemic immunomodulation. Significance: Central nervous system pericytes (perivascular stromal cells) have recently gained significant attention within the scientific community. In addition to being recognized as major players in neurotrauma, pericytes have been discovered to share a common origin and potentially function with traditionally defined mesenchymal stromal cells (MSCs). Although there have been several in vitro comparisons, the in vivo therapeutic application of human brain-derived stromal cells has not been previously evaluated. This study demonstrates that these cells not only display a MSC phenotype in vitro but also have similar in vivo immunomodulatory effects after spinal cord injury that are more potent than those of non-central nervous system tissue-derived cells. Therefore, these cells are of great interest for therapeutic use in spinal cord injury.